REKONSTRUKSI HUKUM ISLAM MELALUI PENDEKATAN KONTESKTUAL: Telaah Komparatif Pemikiran Yudian Wahyudi dan Tariq Ramadan - Zaki Ridho Djakfar, Muhammad; Nurhidayat, Nurhidayat; Sadari, Sadari (Asosiasi Dosen PTKIS Indonesia, 2026)
Relevance for Contemporary Islamic Legal Reform. These two approaches offer inspiration and important lessons for contemporary Islamic legal reform efforts, particularly in the Islamic world facing a deadlock between textual conservatism and secular modernism. First, Opening Space for Modern and Democratic Ijtihad. The idea of rational and collective ijtihad they espouse is crucial for opening up space for Islamic law that is relevant to modern, democratic, and multicultural life. Second, Bridging Islam and the Modern State. Their thinking helps address the tension between Islam and the state, between sharia and the constitution. Both demonstrate that Islam can exist within the framework of a nation-state (Yudian) or a secular state (Ramadan) without losing its values. Third, Instilling Universal Islamic Ethics. Legal reform is not simply a matter of changing the wording of fatwas; it must also address the ethos and universal values of Islam. This is crucial for making Islam a blessing for all the worlds in the global community. Fourth, Inspiration for the Young Intellectual Generation. Their thinking serves as a starting point for the younger generation of Muslims to develop an Islam that is open, reflective, and actively involved in building civilization.